Association of Biomarker Level with Cardiovascular Events: Results of a 4-Year Follow-Up Study. (23rd June 2020) - Turgunova, L.; Baidildina, B.; Laryushina, Y.; Koichubekov, B.; Turmukhambetova, A.; Akhmaltdinova, L.
Abstract : Background . Given the high rates of morbidity and mortality from cardiovascular disease (CVD), the primary and secondary CVD prevention is one of the public health priority. Inflammation and endothelial dysfunction are the major drivers of atherosclerosis development and progression. In this regard, the study of the biomarker application as a tool to better identify high-risk individuals is an up-to-date sector of modern cardiology. The simultaneous measurement of multiple biomarkers can increase the risk stratification for people who are not known to have cardiovascular events in their history. The study aimed to investigate the predictive value of chemokine (C-X-C motif) ligand 16 (CXCL16), endocan, and heart-type fatty acid binding protein (H-FABP) in the cardiovascular event development in people who are not known to have cardiovascular events in their history. Method . We examined 363 people aged 30 to 65 who have been living permanently in the city of Saran, Karaganda region. The selected participants were people registered at a clinic at the city of Saran, who were screened between August and September 2014. Results . The follow-up period was 48 months (from August-September 2014 to November 2018). The results showed that CXCL16 (p < 0.001 ), endocan (p < 0.001 ), and H-FABP (p = 0.002 ) biomarker levels are significantly higher in outcome groups compared with those of the no-outcome group. Univariate regression analysis proved the prognostic significance of all biomarkers in cardiovascular events development. The multivariate regression analysis after the adjustment confirmed that the CXCL16 increase was associated with the "composite endpoint" (CE) development (p < 0.001 ) while the endocan increased due to the development of major cardiovascular events (MACE) (p = 0.008 ); we did not find the association of the risks of event development with the H-FABP level increase (p = 0.83 ).